Understanding the origin of ethanol oxidation from ultrafine nickel manganese oxide nanosheets derived from spent alkaline batteries. (20th November 2022) - Devi, Sapna; Sunaina,; Wadhwa, Ritika; Yadav, Krishna K.; Jha, Menaka
Abstract: With rapid industrialization, there is a tremendous increase in the utilization of electronics. Among various electronics, Zn–MnO2 primary batteries are used in small gadgets in very huge quantity. The disposal of spent electronic batteries via the landfill creates hazardous waste which led to environmental pollution. As spent batteries contain the valuable element, the resource recovery from the spent battery is one of the fascinating areas to meet material for sustainable energy demand. In this work, we have developed a new process for synthesis of Ni6 MnO8 nano-particles via a facile chemical route using manganese chloride derived from the cathode part of the spent battery. The as prepared Ni6 MnO8 has been used for electrochemical ethanol oxidation. The Ni6 MnO8 shows robust electroactivity for ethanol oxidation with high current density (13.69 mAcm −2 ) at low oxidation peak potential (1.53 V), smaller Tafel slope value (61 mV/dec), and high current density ratio (Jf /Jb ) 1.01. The observed surface area of the Ni6 MnO8 sheet (136 m 2 /g) is ∼1.4 times higher than the maximum reported surface area till now (91.32 m 2 /g). The current studies indicate that non-noble metal-based mixed metal oxides derived from waste can be used as a promising anodic material for direct alkaline fuel cells. Graphical abstract: Design of green method for stabilization of ultrafine nickel manganese oxide Ni6 MnO8 nanosheets and study their application in ethanol oxidation. Image 1 Highlights: Ni6 MnO8 sheets assembled from nanoparticles was synthesized using spent battery. Synthesized Ni6 MnO8 exhibited highest surface area in comparison to earlier reports. Ni6 MnO8 has been used for ethanol oxidation (J∼13.69 mAcm −2 ) for the first time. Ni6 MnO8 catalyst is robust and have anti-poisoning property.